The evidence for orthopaedic surgery - Limb, David; Hay, Stuart M. (Tfm Pub., 2007)
The rate of publication of new materials and research exceeds the capacity of any individual to keep fully abreast. So how are we to keep up-to-date and sufficiently informed to practice evidence-based medicine? One way is to rely on authoritative yet unbiased reviews of important questions written by authors dedicated to education of the reader; that is the purpose of this book. It has been a formidable challenge, therefore, for our internationally-based contributors to wade through the sea of evidence and pick out significant advances that represent a true step forward in our knowledge.